Nestin‐expressing cell types in the temporal lobe and hippocampus: Morphology, differentiation, and proliferative capacity. Issue 1 (19th September 2017) - Liu, Joan; Reeves, Cheryl; Jacques, Thomas; McEvoy, Andrew; Miserocchi, Anna; Thompson, Pamela; Sisodiya, Sanjay; Thom, Maria
Abstract: Nestin is expressed in immature neuroepithelial and progenitor cell types and transiently upregulated in proliferative neuroglial cells responding to acute brain injury, including following seizures. In 36 temporal lobe (TLobe) specimens from patients with TLobe epilepsy (age range 8–60 years) we studied the number, distribution and morphology of nestin‐expressing cells (NEC) in the pes, hippocampus body, parahippocampal gyrus, amygdala, temporal cortex and pole compared with post mortem control tissues from 26 cases (age range 12 gestational weeks to 76 years). The proliferative fraction of NEC was evaluated in selected regions, including recognized niches, using MCM2. Their differentiation was explored with neuronal (DCX, mushashi, βIII tubulin, NeuN) and glial (GFAP, GFAPdelta, glutamine synthetase, aquaporin4, EAAT1) markers, both in sections or following culture. Findings were correlated with clinical parameters. A stereotypical pattern in the distribution and morphologies of NEC was observed, reminiscent of patterns in the developing brain, with increased densities in epilepsy than adult controls ( p < .001). Findings included MCM2‐positive radial glial‐like cells in the periventricular white matter and rows of NEC in the hippocampal fimbria and sulcus. Nestin cells represented 29% of the hippocampal proliferative fraction in epilepsy cases; 20% co‐expressed βIII tubulin in culture compared with 28% with GFAP. Significant correlations were noted between age at surgery, memory deficits and nestin populations. TLobe NEC with ongoing proliferative capacity likely represent vestiges of developmental migratory streams and resident reactive cell populations of potential relevance to hippocampal epileptogenesis, TLobe pathology, and co‐morbidities, including memory decline. Main Points: Adult hippocampal nestin‐expressing cells include radial glial with proliferative capacity and glial and neuronal differentiation. They are of relevance to hippocampal epileptogenesis, epilepsy‐related pathologies and comorbidities.